DC 75 [compact disc] : the music of DC Comics : 75th anniversary collection. (Watertower Music : Fontana [distributor], 2010)
Celebrates highlights of DC Comics' rich musical history including many rare theme songs that have never before been released. The compilation begins in 1941 with the theme song from Max Fleischer's Academy Award-nominated Superman cartoons and moves through the decades.